Living conditions of a city-port in western Venezuela (1830 - 1860) (Revista LIDER, 2021)
Cultural, social, and material live conditions are studied in Maracaibo, the most important city-port of the West Venezuela, during the three first decades of the republican period (1830-1860), environment that did not satisfy the aspirations of a minority sector who directed the life of that conglomerate, influenced by the reviving ideas of Illustration and Liberalism. Diverse factors attempted against the possibility to made truth the modernization of 19th century’s metropolis, especially the lack of resources that impeded works and improvements performances. The presence of a majority collective with ancient habits, opposite to the standards that tried to be impose since the elites, expressed in legal instruments devised in the provinces to establish guidelines that should rule public behaviors, reveals the need of regulate activities and routine situations that hindered searching of advance and politeness according to the new ideas and with the importance that went acquiring the city port. This historic reconstruction was performed from regulations, ordinances, laws and official decrees, complemented with chronicles and articles published in the newspapers of that period.